Kepastian Hukum Pengaturan Batas Volume Suara Sound Horeg pada Acara Festival Budaya dan Perlindungan Hukum terhadap Masyarakat - Julian Abel Akasi; Yenny Yuniawaty (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
The phenomenon of using 'sound horeg' at Cultural Festival events in East Java has given rise to disturbances for the community, such as damage to building structures, and health issues because the volume of the sound horeg reaches 135 decibels, which is far exceeding the safe limit set by the WHO, which is 85 decibels. Although there already exists a Joint Circular Letter from the Governor of East Java Number 300.1/6902/209.5/2025, Number SE/1/VIII/2025, and Number SE/10/VIII/2025, as well as a Fatwa from the East Java Indonesian Ulema Council (MUI) Number 1 of 2025, at Cultural Festival events in East Java, the use of sound horeg at a very high volume still persists. Therefore, legal certainty and legal protection are needed for the community regarding the use of sound horeg at Cultural Festival events.This research utilizes the normative juridical method with an approach focusing on statutory regulations (statute approach) and a conceptual approach. The type of research employed is descriptive analytical, as it aims to describe and analyze the legal issues being examined. The data used originates from secondary data, which encompasses primary legal materials, secondary legal materials, and tertiary legal materials.